If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(4x + -7) = 4x + 2x Reorder the terms: 3x(-7 + 4x) = 4x + 2x (-7 * 3x + 4x * 3x) = 4x + 2x (-21x + 12x2) = 4x + 2x Combine like terms: 4x + 2x = 6x -21x + 12x2 = 6x Solving -21x + 12x2 = 6x Solving for variable 'x'. Reorder the terms: -21x + -6x + 12x2 = 6x + -6x Combine like terms: -21x + -6x = -27x -27x + 12x2 = 6x + -6x Combine like terms: 6x + -6x = 0 -27x + 12x2 = 0 Factor out the Greatest Common Factor (GCF), '3x'. 3x(-9 + 4x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-9 + 4x)' equal to zero and attempt to solve: Simplifying -9 + 4x = 0 Solving -9 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 4x = 0 + 9 4x = 0 + 9 Combine like terms: 0 + 9 = 9 4x = 9 Divide each side by '4'. x = 2.25 Simplifying x = 2.25Solution
x = {0, 2.25}
| 3a-5=4+3a | | -2x^2+7x-5=0 | | -4x^2+20x-25=0 | | 12-2w=-22 | | 4x=9x+6 | | -8x-52=4x+32 | | -81+9x=88-4x | | 5=-50(2x-4)-2x | | 5x-63=117-4x | | -x-98=8x+37 | | -6-6x=16-5x | | 3*l= | | -47+2x=44-5x | | 75m-5-50m=1 | | 6(x+2)=5 | | -68+6x=75-5x | | 3(2x+1)-5=14-(x+14) | | -52-6x=3x+38 | | -2x-y=-1 | | -4(-1-2x)=35 | | -56+2x=22+8x | | 7x^2-x-12=0 | | -5x-4(-1-2x)=35 | | -2x-3+8x=-45 | | 32-34(65+56)=670 | | 99-4s-6s=-1 | | 32-6= | | -2x-12=6-3x | | 4nm+2sm-10n-5s=0 | | 4x^2-3x+17=0 | | 16r-8r=-1 | | -6x-68=103+3x |